Intrauterine Zika virus infection of pregnant immunocompetent mice models transplacental transmission and adverse perinatal outcomes - Vermillion, Meghan S.; Lei, Jun; Shabi, Yahya; Baxter, Victoria K.; Crilly, Nathan P.; McLane, Michael; Griffin, Diane E.; Pekosz, Andrew; Klein, Sabra L.; Burd, Irina (Nature communications, 2017)
Zika virus (ZIKV) crosses the placenta and causes congenital disease. Here we develop an animal model utilizing direct ZIKV inoculation into the uterine wall of pregnant, immunocompetent mice to evaluate transplacental transmission. Intrauterine inoculation at embryonic day (E) 10, but not E14, with African, Asian or American strains of ZIKV reduces fetal viability and increases infection of placental and fetal tissues. ZIKV inoculation at E10 causes placental inflammation, placental dysfunction and reduces neonatal brain cortical thickness, which is associated with increased activation of microglia. Viral antigen localizes in trophoblast and endothelial cells in the placenta, and endothelial, microglial and neural progenitor cells in the fetal brain. ZIKV infection of the placenta increases production of IFNβ and expression of IFN-stimulated genes 48 h after infection. This mouse model provides a platform for identifying factors at the maternal–fetal interface that contribute to adverse perinatal outcomes in a host with an intact immune system. Zika virus infection of pregnant women is associated with congenital neurological disorders. Here, Vermillion et al . develop an immunocompetent mouse model for identification of factors at the maternal-fetal interface that contribute to adverse perinatal outcomes.